2020
DOI: 10.1039/c9ra08995k
|View full text |Cite
|
Sign up to set email alerts
|

The biosorptive uptake of enrofloxacin from synthetically produced contaminated water by tamarind seed derived activated carbon

Abstract: The veterinary antibiotic enrofloxacin (ENR), an emerging contaminant, poses great concern due to its ubiquitous nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…4), ACT had an adsorption capacity close to 800 cm 3 g −1 of nitrogen, while ACHT had a lower adsorption capacity, with a value close to 400 cm 3 g −1 . The surface area values were higher than those obtained by Jamion et al 71 and close to the values found by Samanta et al, 72 who reported surface areas of 594 and 962 m 2 g −1 , respectively, when producing activated carbon from raw tamarind seed bran using the same activating agent (phosphoric acid).…”
Section: Characterization Of the Carbonssupporting
confidence: 83%
“…4), ACT had an adsorption capacity close to 800 cm 3 g −1 of nitrogen, while ACHT had a lower adsorption capacity, with a value close to 400 cm 3 g −1 . The surface area values were higher than those obtained by Jamion et al 71 and close to the values found by Samanta et al, 72 who reported surface areas of 594 and 962 m 2 g −1 , respectively, when producing activated carbon from raw tamarind seed bran using the same activating agent (phosphoric acid).…”
Section: Characterization Of the Carbonssupporting
confidence: 83%
“…While the isotherm analysis is important in defining the adsorption process and nature of the adsorbent, the kinetic analysis determines the rate of adsorbate that is adsorbed onto the PKSAC and their mechanistic behavior. Samanta et al 28 . reported that the kinetic analysis is important to identify design information, such as process time per run and equipment sizing.…”
Section: Resultsmentioning
confidence: 99%
“…While the isotherm analysis is important in defining the adsorption process and nature of the adsorbent, the kinetic analysis determines the rate of adsorbate that is adsorbed onto the PKSAC and their mechanistic behavior. Samanta et al 28 reported that the kinetic analysis is important to identify design information, such as process time per run and equipment sizing. Sarker et al 29 further elaborated that the adsorbent that has slow kinetics despite the fact that having a high adsorption capacity is not preferable to be applied at an industrial scale, since a long residence time in an adsorption column (i.e., fixed bed) will be required.…”
Section: Kinetic Analysismentioning
confidence: 99%
“…The rapidity of adsorption found was higher at the starting due to existing of the open and active sites on sorbent surfaces, present in lower dose, brought about faster diffusion of ENX molecules to the adsorbing sites. 13 In this experiment, the other parameters were kept unchanged. time was recorded to reach 16 h (Figure 5f).…”
Section: Impact Of Biosorbent Dosagementioning
confidence: 99%